Sema4D correlates with tumour immune infiltration and is a prognostic biomarker in bladder cancer, renal clear cell carcinoma, melanoma and thymoma. (4th July 2021) - Lu, Qiongyu; Cai, Ping; Yu, Yan; Liu, Ziting; Chen, Guona; Zeng, Zhao
Abstract: Sema4D, a member of the immune semaphorin family, plays crucial roles in the immune regulation, bone resorption and nervous system. It is also involved in angiogenesis and tumour progression. However, systemic studies on the correlation between Sema4D expression and the immune infiltration or clinical outcomes in tumours are still limited. Here, we analysed the landscape of Sema4D expression and its prognostic value in the cancer genome atlas pan-cancer as well as the correlation between Sema4D and immune cell infiltration by Tumour Immune Estimation Resource and Gene Expression Profiling interactive analysis online tools. Results showed that a higher Sema4D expression was significantly correlated with a favourable overall survival in diverse solid tumours including bladder cancer (Hazards Ratio (HR)=0.68, p  = .0095), kidney renal clear cell carcinoma (HR = 0.61, p  = .0016), melanoma (HR = 0.58, p  = 6.6e-05) and thymoma (HR = 0.1, p  = .011). Interestingly, Sema4D expression has positive correlation with various tumour infiltrating immune cells and immune cell biomarkers in these tumours. These results suggest that Sema4D could be a prospective biomarker for calculating hazard ratio of tumour patients and their tumour immune infiltration levels.